Dendritic cells during Epstein Barr virus infection - Christian, Münz (Frontiers in Microbiology, 2014)
Epstein Barr virus (EBV) causes persistent infection in more than 90% of the human adult population and is associated with 2% of all tumors in humans. This γ-herpes virus infects primarily human B and epithelial cells, but it has been reported to be sensed by dendritic cells (DCs) during primary infection. These activated DCs are thought to contribute to innate restriction of EBV infection and initiate EBV-specific adaptive immune responses via cross-priming. The respective evidence and their potential importance for EBV-specific vaccine development will be discussed in this review.